Perspectives in immunotherapy: meeting report from the “Immunotherapy Bridge”, Napoli, November 30th 2016 - Ascierto, Paolo A. (J Transl Med, 2017)
The complex interactions between the immune system and tumors lead the identification of key molecules that govern these interactions: immunotherapeutics were designed to overcome the mechanisms broken by tumors to evade immune destruction. After the substantial advances in melanoma, immunotherapy currently includes many other type of cancers, but the melanoma lesson is essential to progress in other type of cancers, since immunotherapy is potentially improving clinical outcome in various solid and haematologic malignancies. Monotherapy in pre-treated NSCLC is studied and the use of nivolumab, pembrolizumab and atezolizumab as second-line of advanced NSCLC is demonstrated as well as first line monotherapy and combination therapy in metastatic NSCLC studied. Patients with HNSCC have immunotherapeutic promises as well: the FDA recently approved moAbs targeting immune checkpoint receptors. Nivolumab in combination with ipilumumab showed acceptable safety and encouraging antitumor activity in metastatic renal carcinoma. HCCs have significant amounts of genomic heterogeneity and multiple oncogenic pathways can be activated: the best therapeutic targets identification is ongoing. The treatment of advanced/relapsed EOC remain clearly an unmet need: a better understanding of the relevant immuno-oncologic pathways and their corresponding biomarkers are required. UC is an immunotherapy-responsive disease: after atezolizumab, three other PD-L1/PD-L1 inhibitors (nivolumab, durvalumab, and avelumab) were approved for treatment of platinum-refractory metastatic urothelial carcinoma. Anti-PD-1/PD-L1 monotherapy is associated with a modest response rate in metastatic breast cancer; the addition of chemotherapy is associated with higher response rates. Immunotherapy safety profile is advantageous, although, in contrast to conventional chemotherapy: boosting the immune system leads to a unique constellation of inflammatory toxicities known as immune-related Adverse Events (irAEs) that may warrant the discontinuation of therapy and/or the administration of immunosuppressive agents. Research should explore better combination with less side effects, the right duration of treatments, combination or sequencing treatments with target therapies. At present, treatment decision is based on patient’s characteristics.